Dao (diaminoxidase) purification from natural sources and enzyme-enriched food production - Burak Durmaz; Erhan Canbay; Şüra Öztürk Baykan; Hatice Kalkan Yıldırım; Eser Yıldırım Sözmen (Applied Food Research)
Histamine intolerance, affecting approximately 1–3 % of the population, is linked to elevated histamine levels that can mimic allergic reactions. Diamine oxidase (DAO) plays a key role in histamine degradation. This study aimed to purify a plant-derived DAO enzyme with higher specific activity than commercial supplements and to apply it in fermented foods, specifically pickles, widely consumed in Turkish cuisine.DAO was extracted from wheatgrass produced from a local cultivar registered by the Aegean Agricultural Research Institute. The enzyme was purified using ammonium sulfate precipitation and dialysis. Enzyme activity and histamine levels were quantified using LC/MS-MS. Wheatgrass DAO showed a specific activity of 10.18 U/mg in the crude extract and increased to 207.6 U/mg after dialysis.To assess its functionality, DAO (both commercial and plant-derived) was added at various concentrations during pickle fermentation. After three weeks, herbal DAO reduced histamine levels in pickle juice by up to 96 %, significantly outperforming the commercial enzyme in most cases. This is the first reported application of wheatgrass-derived DAO in food fermentation (Patent No: P-201,710). The findings suggest a promising natural solution for reducing histamine in fermented foods, offering a dietary alternative for individuals with histamine intolerance.